Surface Modification of Bi2Te3 Nanoplates Deposited with Tin, Palladium, and Tin/Palladium Using Electroless Deposition - Kaito Kohashi; Yutaro Okano; Daiki Tanisawa; Keisuke Kaneko; Shugo Miyake; Masayuki Takashiri (Crystals, 2024)
Surface-modified nanoplate-shaped thermoelectric materials can achieve good thermoelectric performance. Herein, single-crystalline Bi2Te3 nanoplates with regular hexagonal shapes were prepared via solvothermal techniques. Surface modification was performed to deposit different metals onto the nanoplates using electroless deposition. Nanoparticle-shaped tin (Sn) and layer-shaped palladium (Pd) formed on the Bi2Te3 nanoplates via electroless deposition. For the sequential deposition of Sn and Pd, the surface morphology was mostly the same as that of the Sn-Bi2Te3 nanoplates. To assess the thermoelectric properties of the nanoplates as closely as possible, they were compressed into thin bulk shapes at 300 K. The Sn-Bi2Te3 and Sn/Pd-Bi2Te3 nanoplates exhibited the lowest lattice thermal conductivity of 1.1 W/(m·K), indicating that nanoparticle-shaped Sn facilitated the scattering of phonons. By contrast, the Pd-Bi2Te3 nanoplates exhibited the highest electrical conductivity. Thus, the highest power factor (15 μW/(m∙K2)) and dimensionless ZT (32 × 10−3) were obtained for the Pd-Bi2Te3 nanoplates. These thermoelectric properties were not as high as those of the sintered Bi2Te3 samples; however, this study revealed the effect of different metal depositions on Bi2Te3 nanoplates for improving thermoelectric performance. These findings offer venues for improving thermoelectric performance by sintering nanoplates deposited with appropriate metals.